Audit Efficiency and Influence of Environmental Factors to State Bodies: Evidence of Kazakhstan - SEMBAYEV, Dauren (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.12.5(53).16, 2021)
Research and assessment of the public sector debt management system and the development of audit methods based on them will improve the process of monitoring the effectiveness of the formation, management and assessment of public debt. In accordance with the provided data of the audit of the audit of the effectiveness of the formation and management of debt of the Government of the Republic of Kazakhstan, an assessment of the state of the state and state-guaranteed debt was carried out. A negative trend in the growth of public debt and the lack of control and management of public and guaranteed public debt, which is reflected in the growth of both nominal and percentage ratio of debt to GDP, are noted, as well as trends in environmental and social issues of both global and regional scale, which are possible to solve only on condition of creating a new type of ecological culture, greening education in accordance with the actual needs of the individual and civil society.